Evaluation of Growth Performance and Economic Return Analysis of Bathua (Chenopodium album) Genotypes - Momin, Md. Abdul; Islam, A.F.M. Saiful; Uddin, Md. Sharaf; Alom, Jahirul; Monshi, Mahadi Hasan (Journal of Tropical Crop Science, 2023)
Bathua (Chenopodium album), a fast-growing weedy annual plant under the genus Chenopodium, is valuable for its high nutritional, medicinal and economic values as a leafy vegetable. The present study was carried out to evaluate the growth performance and economic returns of bathua genotypes in acid soil at Sylhet, Bangladesh. The experiment was laid out in a randomized complete block design with three replications. Morphological and growth parameters were recorded at the final harvest. The maximum plant height, number of branches per plant, fresh weight of inflorescence and leaf length were recorded in local bathua 1(110.5 cm, 65.33, and 8.93 g, respectively). The maximum fresh weight of leaves per plant, the maximum dry weight of leaves per plant were recorded in local bathua 2 (39.92 g and 8.79 g respectively). Results revealed that the studied morphological parameters including plant height, fresh and dry weight of leaves per plant, fresh and dry weight of stem per plant, fresh and dry weight of inflorescence per plant, stem base diameter, number of leaves per plant, number of branches per plant and leaf length influences the foliage yield of bathua. The highest foliage yield (9.20 t.ha-1), total gross return (Tk.552000.ha-1), net return (Tk.367000.ha-1) and BCR (2.98) were found in local bathua 1. From the findings of the present study, local bathua 1 could achieve higher productivity and profitability in acid soils of Sylhet, Bangladesh.